Succinyl-CoA Synthetase: New Antigen Candidate of Bartonella bacilliformis. - Cláudia Gomes; Noemí Palma; Maria J Pons; Ariel Magallón-Tejada; Isabel Sandoval; Carmen Tinco-Valdez; Carlos Gutarra; Juana Del Valle-Mendoza; Joaquim Ruiz; Mayumi Matsuoka (Public Library of Science (PLoS), 2016)
Bartonella bacilliformis is the causative agent of Carrion's disease, a neglected illness with mortality rates of 40-85% in the absence of treatment. The lack of a diagnostic technique to overcome misdiagnosis and treat asymptomatic carriers is of note. This study aimed to identify new B. bacilliformis antigenic candidates that could lead to a new diagnostic tool able to be implemented in endemic rural areas.Blood (n = 198) and serum (n = 177) samples were collected in northern Peru. Clinical data were recorded. Specific 16S rRNA amplification by RT-PCR, IFA and ELISA for IgM/IgG with whole cells as antigens was done. Western blot analysis and N-terminal amino acid sequencing detected seroreactive proteins. ELISAs for IgM/IgG for the antigenic candidates were performed. Of the population 33.3% reported at least one symptom compatible with Carrion's disease; 25.4% (IFA), 27.1% (ELISA-IgG), 33.9% (ELISA-IgM) and 38.9% (RT-PCR) of samples were positive. Four proteins were considered potential antigenic candidates, including two new antigenic candidates, succinyl-CoA synthetase subunit α (SCS-α) and succinyl-CoA synthetase subunit β (SCS-β). On Western blot both Pap31 and SCS-α interacted with IgM, while GroEL and SCS-β interacted with IgG. The presence of specific antibodies against the antigenic candidates varied from 34.5% (IgG against SCS-α) to 97.2% (IgM against Pap31).RT-PCR and the high levels of positivity for specific ELISAs demonstrate high levels of B. bacilliformis exposure and asymptomatic carriers among inhabitants. The new antigens identified might be used as a new rapid diagnostic tool to diagnose acute Carrion's disease and identify asymptomatic carriers.